Investigation of wind effect reduction on square high-rise buildings by corner modification. Issue 6 (April 2019) - Li, Yi; Li, Yong-Gui; Li, Qiu-Sheng; Tee, Kong-Fah
Although empirical formulas have been provided in relevant design code for estimating wind loads and wind-induced responses on square high-rise buildings, the effects of corner modification treatments on wind loads and wind-induced responses of square high-rise buildings need to be evaluated quantitatively. In this study, wind pressure measurements for a benchmark square high-rise building and three corner modified square high-rise buildings were first carried out to acquire the spatial-temporal varying pressure distributions. Moreover, the corresponding full-scale finite element models were established in ANSYS software to get their dynamic properties. Combined with wind tunnel test results and modal analysis, wind loads and wind-induced responses of the four square high-rise buildings were calculated and compared for designing the best aerodynamic treatment of reducing wind effects on square high-rise buildings. This article aims to provide visual comparisons of wind effect reduction for structural designers and owners of square high-rise buildings.